Forming Benzylic Iodides via a Nickel Catalyzed Diastereoselective Dearomative Carboiodination Reaction of Indoles. Issue 15 (12th March 2019) - Marchese, Austin D.; Lind, Florian; Mahon, Áine E.; Yoon, Hyung; Lautens, Mark
Abstract: A diastereoselective dearomative carboiodination reaction is reported. We report a novel metal‐catalyzed approach to install reactive secondary benzylic iodides. Utilizing the unique reactivity of nickel, we have expanded the carboiodination reaction to non‐activated aromatic double bonds forming a previously unattainable class of iodides. We also report a broadly applicable method to avoid the use of a metallic reducing agent by utilizing an alkyl phosphite as the ligand. The reaction is thought to proceed through a syn intramolecular carbonickelation across a 2‐substituted indole followed by a diastereoretentive reductive elimination of the carbon−iodine bond. The complex iodinated indolines generated in the reaction were obtained in moderate to good yields and good to excellent diastereoselectivity. The products were easily functionalized by a variety of synthetic methods. Abstract : A diastereoselective dearomative carboiodination reaction is reported. Utilizing the unique reactivity of nickel, the carboiodination reaction was expanded to non‐activated aromatic double bonds to form a previously unattainable class of iodides. Furthermore, a broadly applicable method to avoid the use of a metallic reducing agent by utilizing an alkyl phosphite as the ligand is reported.